A soft robotic total artificial hybrid heart - Maziar Arfaee; Annemijn Vis; Paul A. A. Bartels; Lucas C. van Laake; Lucrezia Lorenzon; Dina M. Ibrahim; Debora Zrinscak; Anthal I. P. M. Smits; Andreas Henseler; Matteo Cianchetti; Patricia Y. W. Dankers; Carlijn V. C. Bouten; et al. (Nature Communications)
Abstract End-stage heart failure is a deadly disease. Current total artificial hearts (TAHs) carry high mortality and morbidity and offer low quality of life. To overcome current biocompatibility issues, we propose the concept of a soft robotic, hybrid (pumping power comes from soft robotics, innerlining from the patient’s own cells) TAH. The device features a pneumatically driven actuator (septum) between two ventricles and is coated with supramolecular polymeric materials to promote anti-thrombotic and tissue engineering properties. In vitro, the Hybrid Heart pumps 5.7 L/min and mimics the native heart’s adaptive function. Proof-of-concept studies in rats and an acute goat model demonstrate the Hybrid Heart’s potential for clinical use and improved biocompatibility. This paper presents the first proof-of-concept of a soft, biocompatible TAH by providing a platform using soft robotics and tissue engineering to create new horizons in heart failure and transplantation medicine.